Second Five Year Plan Progress Report for 1957-58 Government of Rajasthan - Planning Commission (Planning Commission, 1957)
The stresses and strains in the economy, visible from the very beginning of the Second Five Year Plan, became prominent during the year 1957-58. the inflationary tendencies, being the cumulative result of the high tempo of activities in pursuance of the Five Year Plans, were further accentuated. the food and price situation, the balance of payments difficulties and the problems of mobilizing both the internal and external resources to finance the Plan, all came up for critical review. As a result, various corrective measures were taken on the fiscal, monetary and foreign exchange fronts which had their impact, though not very lasting, on the general economic situation towards the later half of the year under report. the result of all these was a curious admixture of basically expansionist trends with certain recessionary symptoms. the spiral of rising prices, which began since May. 1955. continued, with slight intervening short lived interruptions, almost till the middle of the year under report.
Directorate of Economics and Statistics, Government of Rajasthan